2021
DOI: 10.1111/evj.13417
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chlorhexidine and alcohol‐based antisepsis of the distal limbs of horses

Abstract: Background: An alcohol-based rub has been confirmed effective at reducing bacterial counts on equine skin. Skin sites with expected high bacterial burden have not been tested or has a comparison to a common protocol been performed. Objectives:To determine if ethanol-based antisepsis reduces bacterial counts on the equine distal limb comparable to a current chlorhexidine scrub method and determine the most effective application technique for the product. Study design: Randomised trial.Methods: Forty-one horses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The lack of adverse skin reaction and similar performance of both alcohol‐based protocols when compared with the CHG protocol in our study provide evidence to support skin preparation with alcohol‐based antiseptics in cattle. Previous studies in horses have also confirmed the application of alcohol‐based antiseptics are well tolerated in veterinary species 7,8,10 . Pre‐existing dermatitis or the presence of wounds may increase adverse skin reactions and could potentially affect bacterial reduction when using alcohol‐based antiseptic protocols and further clinical investigation is warranted.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The lack of adverse skin reaction and similar performance of both alcohol‐based protocols when compared with the CHG protocol in our study provide evidence to support skin preparation with alcohol‐based antiseptics in cattle. Previous studies in horses have also confirmed the application of alcohol‐based antiseptics are well tolerated in veterinary species 7,8,10 . Pre‐existing dermatitis or the presence of wounds may increase adverse skin reactions and could potentially affect bacterial reduction when using alcohol‐based antiseptic protocols and further clinical investigation is warranted.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies in horses have also confirmed the application of alcoholbased antiseptics are well tolerated in veterinary species. 7,8,10 Pre-existing dermatitis or the presence of wounds may increase adverse skin reactions and could potentially affect bacterial reduction when using alcohol-based antiseptic protocols and further clinical investigation is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation